2011
DOI: 10.5433/1679-0359.2010v31n4sup1p1337
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevivência e desenvolvimento in vitro de Cattleya (Orchidaceae) submetida a tratamentos com colchicina

Abstract: ResumoNas orquidáceas, a poliploidia produz características desejáveis, que se traduzem em aumento das peças florais, grau de suculência, intensificação do colorido, durabilidade e maior resistência das flores. A colchicina como agente indutor de poliploidia em cultura de plantas in vitro tem suas limitações, pois em elevadas concentrações ou tratamentos muito prolongados, torna-se tóxica. O objetivo do trabalho foi avaliar a influência da concentração e do tempo de exposição à colchicina, na sobrevivência e n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The identified tetraploids recovered normal growth in subsequent culture. A similar result was found for Cattleya (Orchidaceae); the optimal concentration of the colchicine solution ranged from 125 to 250 mM, but the durations might be different for each species (de Mello e Silva et al 2000;Huy et al 2019;Lone et al 2010;Wu et al 2020). Although the solid medium with colchicine treatment showed higher lethality, it is possible to obtain tetraploids in lower concentrations, thus reducing the amount of expensive and toxic colchicine necessary.…”
Section: Discussionsupporting
confidence: 69%
“…The identified tetraploids recovered normal growth in subsequent culture. A similar result was found for Cattleya (Orchidaceae); the optimal concentration of the colchicine solution ranged from 125 to 250 mM, but the durations might be different for each species (de Mello e Silva et al 2000;Huy et al 2019;Lone et al 2010;Wu et al 2020). Although the solid medium with colchicine treatment showed higher lethality, it is possible to obtain tetraploids in lower concentrations, thus reducing the amount of expensive and toxic colchicine necessary.…”
Section: Discussionsupporting
confidence: 69%
“…High concentrations or long periods of exposure to these substances are usually observed to cause phytotoxic effects -generating high mortality among treated seedlings-and tolerance to colchicine and oryzalin varies among species and varieties, depending upon their genetic make up (Vakili, 1962;Ganga and Chezhyan, 2002). Colchicine toxicity at high dosages was reported by Lone et al (2010), who found lower survival rates of the protocorms of Cattleya tigrina (32%) that had been treated with 1 g.L -1 colchicine for 72 h. Regeneration rates of 27.26 % after colchicine exposure were observed in Tagetes erecta (Sajjad et al, 2013). Regeneration rates of 37 and 67% were observed in explants of Aframomum corrorima treated for 7 days with colchicine and oryzalin respectively (Wannakrairoj and Wondyifraw, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…Lone et al [ 26 ] observed a reduction in the survival rate of protocorms of Cattleya tigrina at the highest concentration of colchicine (1%), showing survival rates of 100%, 96% and 84%, with 24, 48 and 72 h of exposure, respectively, and compared to the control (100%). Similar results were reported for Vanda (Orchidaceae) protocorms treated with colchicine, aiming to induce polyploidy.…”
Section: Discussionmentioning
confidence: 99%